Sturge–Weber syndrome: updates in translational neurology - Solomon, Chase; Comi, Anne (Frontiers in Neurology, 2024)
Sturge–Weber syndrome (SWS) is a rare congenital neurovascular disorder that initially presents with a facial port-wine birthmark (PWB) and most commonly associated with a R183Q somatic mosaic mutation in the gene GNAQ. This mutation is enriched in endothelial cells. Contrast-enhanced magnetic resonance imaging (MRI) diagnoses brain abnormalities including leptomeningeal vascular malformation, an enlarged choroid plexus, and abnormal cortical and subcortical blood vessels. Mouse SWS models identify dysregulated proteins important for abnormal vasculogenesis and blood brain barrier permeability. Recent clinical research has focused on early diagnosis, biomarker development, presymptomatic treatment, and development of novel treatment strategies. Prospective pilot clinical drug trials with cannabidiol (Epidiolex) or with sirolimus, an mTOR inhibitor, indicate possible reductions in seizure frequency and improved cognitive outcome. This review connects the most recent molecular research in SWS cell culture and animal models to developing new treatment methods and identifies future areas of research.